Development of a new method for manufacturing hollow fibre-reinforced plastic structures for aeronautical applications using structural CFRP cores. (14th September 2022) - Rief, Thomas; Motsch-Eichmann, Nicole; May, David; Hausmann, Joachim
ABSTRACT: Currently applied manufacturing technologies for hollow composite structures impose design restrictions, such as limited integration potential, whereas differential designs are limited regarding lightweight design and load transfer due to the need of joints. This paper introduces the patented concept of structural carbon fibre-reinforced polymer (CFRP) cores, intending to overcome limitations allowing for integral, yet complex designs. The hollow cores are initially manufactured and partially cured via resin transfer moulding (RTM) with inflatable rubber core. These cores are then integrated in a dry textile-based preform which is impregnated in another RTM process. Here, the cores stabilize the preform during injection and afterwards remain in the component as load-carrying elements. Thereby the partial degree of cure of the cores before the second RTM process is optmised to balance dimensional stability and bonding strength. The process route using structural CFRP cores was successfully applied to a generic structure and proven by structural testing.